ChemInform Abstract: Copper‐Catalyzed Perfluoroalkylthiolation of Alkynes with Perfluoroalkanesulfenamides. Issue 49 (17th November 2016) - Tlili, Anis; Alazet, Sebastien; Glenadel, Quentin; Billard, Thierry
Abstract: The direct perfluoroalkylthiolation of terminal alkynes is readily achieved with sulfenamide reagents of type (II) and (IV) in the presence of Cu(I)‐catalyst.